Posttraumatic growth as positive personality change: evidence, controversies and future directions - Jayawickreme, Eranda; Blackie, Laura E.R. (Wiley, 2014)
This target article focuses on the construct of post-traumatic growth—positive psychological change experienced as a result of the struggle with highly challenging life circumstances. Prominent theories of post-traumatic growth define it in terms of personality change, and as a result, this area of research should be of great interest to personality psychologists. Despite this fact, most of the research on this topic has not been sufficiently informed by relevant research in personality psychology, and much of the extant research suffers from significant methodological limitations. We review the literature on post-traumatic growth, with a particular focus on how researchers have conceptualized it and the specific methodological issues associated with these conceptualizations. We outline some ways in which personality science can both be enriched by the study of this phenomenon and inform rigorous research on post-traumatic growth and provide a series of guidelines for future research of post-traumatic growth as positive personality change.